Universal screening for substance use by Peer Support Specialists in the Emergency Department is a pathway to buprenorphine treatment - Alex K. Gertner; Kate E. Roberts; Grayson Bowen; Brenda L. Pearson; Robyn Jordan (Addictive Behaviors Reports, 2021)
Introduction: Evidence suggests emergency department (ED)-initiated buprenorphine as efficacious in connecting ED patients to Medications for Opioid Use Disorder (MOUD) utilizing peer support specialists (PSS). However, there are no reports of implementation of ED-initiated buprenorphine in practice. Such information is crucial to support the adoption of ED-initiated buprenorphine. Methods: In this quality improvement pilot study, a PSS screened ED patients over age 18 with the Tobacco, Alcohol, Prescription medication, and other Substance use – 1 (TAPS-1). The PSS considered the patient a positive screen if the patient met the following criteria: risky weekly alcohol use, illicit drugs, or prescription drugs. For patients who screened positive, the PSS delivered a brief intervention and assessed interest in treatment. An ED clinician assessed patients who screened positive for heroin/opioid use and were interested in treatment for buprenorphine induction. Results: From January through June 2019, 1037 patients were screened for risky substance use, and, of these, 238 (23%) screened positive. The distribution of primary substance used was: 51% alcohol, 26% cannabis, 7.5% cocaine, 7.5% heroin, and 3.3% prescription opioids. Of the 23 patients who screened positive for heroin/opioid use and requested treatment, seven were admitted to the hospital. Of the remaining 16 patients, 14 patients wanted buprenorphine treatment, seven were provided buprenorphine in the ED, and four of these attended their intake appointments for community-based MOUD treatment. Conclusion: ED-initiated buprenorphine facilitated by a PSS is feasible and requires coordination and planning. Approaches to ED-initiated buprenorphine that screen only for opioid use will miss many patients interested in substance use treatment.11 This work was supported by North Carolina Department of Human Health Services, Division of Public Health, Injury and Violence Prevention Branch.